Small Particle Fluorescence and Light Scatter Calibration Using FCMPASS Software. Issue 1 (16th September 2020) - Welsh, Joshua A.; Jones, Jennifer C.
Abstract: Use of flow cytometry to analyze small particles has been implemented for several decades. More recently, small particle analysis has become increasingly utilized owing to the increased sensitivity of conventional and commercially available flow cytometers along with growing interest in small particles such as extracellular vesicles (EVs). Despite an increase in small particle flow cytometry utilization, a lack of standardization in data reporting has resulted in a growing body of literature regarding EVs that cannot be easily interpreted, validated, or reproduced. Methods for fluorescence and light scatter standardization are well established, and the reagents to perform these analyses are commercially available. Here, we describe FCMPASS, a software package for performing fluorescence and light scatter calibration of small particles while generating standard reports conforming to the MIFlowCyt‐EV standard reporting framework. This article covers the workflow of implementing calibration using FCMPASS as follows: acquisition of fluorescence and light scatter calibration materials, cataloguing the reference materials for use in the software, creating cytometer databases and datasets to associate calibration data and fcs files, importing fcs files for calibration, inputting fluorescence calibration parameters, inputting light scatter calibration parameters, and applying the calibration to fcs files. Published 2020. U.S. Government. Basic Protocol 1 : Acquisition and gating of light scatter calibration materials Basic Protocol 2 : Acquisition and gating of fluorescence calibration materials Alternate Protocol : Cross‐calibration of fluorescence reference materials Basic Protocol 3 : Cataloguing light scatter calibration materials Basic Protocol 4 : Cataloguing fluorescence calibration materials Basic Protocol 5 : Creating cytometer databases and datasets Basic Protocol 6 : Importing fcs files Basic Protocol 7 : Fluorescence calibration Basic Protocol 8 : Light scatter calibration Basic Protocol 9 : Performing and reporting fcs file calibration